Parâmetros geotécnicos estáticos e dinâmicos de areias quartzosa e carbonatadas - Gomes, Naiala Fidelis (2020)
Proper understanding of the behavior of offshore wind tower foundations (TEO) requires physical and numerical simulations. These structures operate under cyclic loads at low levels of shear strains and in this context, the main parameters involved are the shear modulus and damping, which vary with the strain magnitude. There are several ways to obtain these dynamic parameters and the Resonant Column and Bender Elements tests are the most used. Laboratory tests were carried out encompassing the physicalchemical and mineralogical characterization, and strength tests, as well as the dynamic tests of the Resonant Column and the Bender Element tests. There are sands that have in their chemical composition Calcium Carbonate (CaCO3). These are known as carbonated sands and are abundant in coastal areas and on continental shelves in tropical and temperate regions of the world and present a behavior different from quartz sands. The present research aims to study the static and dynamic parameters of quartz and carbonated sands and to evaluate the behavior of these soils aiming for the application in offshore wind tower foundations projects. The comparison of experimental results with analytical models indicated that some of these models are adequate to predict the dynamic behavior of the sands studied here.